ELF Propagation Measurements (Phase III - Fall 1971). - White,David P. (1972)
The third set in a series of ELF propagation measurements was undertaken to determine the parameters for propagation in the 40 and 70 Hz range. The test period was from 12 October to 3 November 1971. During this interval the transmitter in Wisconsin (WTF) radiated simple sinusoidal signals for two eight-hour periods per day. Receiver sites were located in Utah, Greenland and Norway. Estimates of the average attentuation rate, and the excitation factor were determined. It has been found that the auroral path segment (between Greenland and Norway) gave rise to results which are slightly different from those measured on earlier tests. (Author) See also Report on Phase 2, AD-739 871.